(untitled) (Revista de Administração, 2012)
This article analyzes competence development experiences and the professional recognition of disabled individuals who are already part of an organization, taking into account the main actors involved in this process. It is based on a qualitative case study, carried out in a pharmaceutical multinational in the city of São Paulo. The aim of the study was to describe and discuss the formal practices of this organization for the professional development of disabled people (DPs), as well as the informal experiences of the latter in this firm. Moreover, it analyzes the articulation with the external actors also involved in the process: the pharmaceutical industries union and a Non-Governmental Organization (NGO) specialized in DPs. The results problematize the initiative of promoting a process of constructing and developing competences by means of formal or informal experiences and self-improvement that is specifically for DPs. The experience studied here showed that in this initiative, assumptions about the limitations caused by the biological characteristics of the individuals prevailed. The development practices have sometimes failed to deal with the potential of these professionals, who have progressed little, given the possibilities offered by the organization. Another relevant result is that although there is some articulation between the company and the external agents, there is no effective dialogue or partnership that might enable the process of inclusion and development of DPs to advance. Finally, the study presented elements to encourage thinking on the conduction and implications of organizational programs for DPs. These programs might foster progress or merely encourage the maintenance of the status quo of DPs in the corporation.